2020
DOI: 10.3389/fpsyt.2020.571179
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Depression, Health Beliefs, and Face Mask Use During the COVID-19 Pandemic

Abstract: The 2019 novel coronavirus (COVID-19) pandemic is associated with increases in psychiatric morbidity, including depression. It is unclear if people with depressive symptoms understand or apply COVID-19 information differently to the general population. Therefore, this study aimed to examine associations between depression, health beliefs, and face mask use during the COVID-19 pandemic among the general population in Hong Kong. This study gathered data from 11,072 Hong Kong adults via an online survey. Responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 40 publications
6
41
1
Order By: Relevance
“…These findings may imply that pandemic-related government efficacy serves as a protective factor against the development of PSU among Chinese adults regardless of their gender, age, and educational level. The findings are also consistent with previous empirical evidence that pandemic-related self-efficacy bears a potential effect on promoting adherence to precautionary measures and lowering psychological distress during the pandemic [ 58 , 59 ]. However, pandemic-related self-efficacy did not significantly add to the explained variance in PSU beyond the demographic effects.…”
Section: Discussionsupporting
confidence: 90%
“…These findings may imply that pandemic-related government efficacy serves as a protective factor against the development of PSU among Chinese adults regardless of their gender, age, and educational level. The findings are also consistent with previous empirical evidence that pandemic-related self-efficacy bears a potential effect on promoting adherence to precautionary measures and lowering psychological distress during the pandemic [ 58 , 59 ]. However, pandemic-related self-efficacy did not significantly add to the explained variance in PSU beyond the demographic effects.…”
Section: Discussionsupporting
confidence: 90%
“…This study has interesting findings that involve interpretations in the context of the initial outbreak and in comparison with other studies. Spearman analysis and the SEM showed that some COVID-19–related cognitions (perceived chance of controlling COVID-19 and perceived risks of infection) were significantly associated with both mental distress due to COVID-19 and depressive symptoms; such findings corroborate with other studies [ 15 , 20 - 23 ]. However, it is unexpected that perceived bodily damages (a reflection of perceived severity) and perceived airborne transmission (possibly a misconception) were not significantly correlated with mental distress due to COVID-19 and depression, while such correlations were significant in similar H1N1 research [ 7 , 8 ].…”
Section: Discussionsupporting
confidence: 89%
“…For instance, the four Chinese university student studies conducted during the initial outbreak mainly mentioned lifestyle factors such as sleep and psychological attributes such as resilience but not COVID-19 cognitive factors [ 11 - 14 ]. Several studies of the population in China and overseas looked at cognitive factors such as perceived susceptibility and severity, which were positively associated with depression [ 15 , 20 - 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite such resemblances, the COVID-19 pandemic is an unprecedented crisis in terms of the scope of its influence on both physical and mental health [e.g., ( 8 , 9 )]. To curb the transmission of this hitherto unknown virus, governments all over the world have enforced strict epidemic-control measures such as nationwide school closures, stay-at-home orders, and physical distancing regulations in public areas ( 10 ).…”
Section: Introductionmentioning
confidence: 99%